The effect of counteranions on the molecular structures of phosphanegold(i) cluster cations formed by polyoxometalate (POM)-mediated clusterization. Issue 34 (11th August 2016) - Nagashima, Eri; Yoshida, Takuya; Matsunaga, Satoshi; Nomiya, Kenji
Abstract : In intercluster compounds composed of phosphanegold(i ) cluster cations and polyoxometalate (POM) anions, the POM anions were successfully exchanged with smaller anions such as PF6 − and OTf − . Abstract : The effect of counteranions on the molecular structures of phosphanegold(i ) cluster cations formed by polyoxometalate (POM)-mediated clusterization was investigated. A novel intercluster compound, [(AuLCl )2 (μ-OH)2 ]3 [α-PMo12 O40 ]2 ·3EtOH (1-PMo12 ), was obtained as orange-yellow plate crystals in 12.0% yield from a 6 : 1 molar ratio reaction of the monomeric phosphanegold(i ) carboxylato complex [Au( RS -pyrrld)(LCl )] ( RS -Hpyrrld = RS -2-pyrrolidone-5-carboxylic acid; LCl = tris(4-chlorophenyl)phosphane) in CH2 Cl2 with the free acid-form of Keggin polyoxometalate (POM), H3 [α-PMo12 O40 ]·14H2 O. An EtOH/H2 O (5 : 1, v/v) solvent mixture was used. The dimeric cation [(AuLCl )2 (μ-OH)2 ] 2+ in1-PMo12 was in a parallel-edge arrangement that was formed by self-assembly through the inter-cationic aurophilic interactions of the μ-OH-bridged dinuclear phosphanegold(i ) cation. The POM anion in1-PMo12 was successfully exchanged with a smaller PF6 − anion by the use of an anion-exchange resin. POM-free, colorless block crystals of [(AuLCl )3 (μ3 -O)2 ](PF6 )2 ·4CH2 Cl2 (2-PF6 ) were obtained by vapor diffusion in 14.1% yield. During the synthesis of2-PF6, a compound with mixed counteranions (one POM and one PF6 − anion), i.e. [(AuLCl )4 (μ4 -O)]2 [α-PMo12 O40 ]PF6 (3-PMo12 PF6 ), was obtained in 66.4% yield. Both products were characterized by elemental analysis, TG/DTA, FT-IR, 31 P 1 H NMR, 1 H NMR, and X-ray crystallography. X-ray crystallography revealed that the countercation in2-PF6 was the dimeric cation of the μ3 -O-bridged trisphosphanegold(i ) species, whereas that in3-PMo12 PF6 consisted of an unusual μ4 -O-bridged tetragonal-pyramidal tetrakisphosphanegold(i ) cation. Therefore, we concluded that the POM anion significantly contributed to the stabilization of these countercations (parallel-edged arrangement in1-PMo12 and μ4 -O-bridged tetragonal-pyramid in3-PMo12 PF6 ). Moreover, the previously reported yellow crystals of [(AuLF )2 (μ-OH)2 ]3 [PMo12 O40 ]2 ·3EtOH (4-PMo12 : LF = tris(4-fluoro phenyl)phosphane) were successfully converted to the POM-free crystalline OTf − salt [(AuLF )2 (μ-OH)2 ](OTf)2 ·0.5Et2 O (4-OTf ) by the use of an anion-exchange resin. X-ray crystallography also revealed that the parallel-edge arrangement of the dimeric cation in4-PMo12 was converted to the crossed-edge arrangement of that in4-OTf . These results illustrate that the Au⋯OPOM and hydrogen-bonding (C–H⋯OPOM and O–H⋯OPOM ) interactions between the phosphanegold(i ) cluster cation and the Keggin POM anion in the solid state significantly contribute to the structure, composition, and stability of the phosphane gold(i ) cluster cations in4-PMo12 .